(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This scientific article provides a comprehensive analysis of the biological characteristics, chemical composition, and positive effects of fig (Ficus carica L.) fruits on the human body. The physiological significance of macro- and microelements, vitamins, antioxidants, enzymes, and dietary fiber contained in figs is scientifically examined. The results of the study indicate that figs can be recommended as an important food product for dietary nutrition, disease prevention, and the promotion of a healthy lifestyle.